What is the standard form of y=(x-13)(x-12)?

balastantpef

balastantpef

Answered

2022-02-03

What is the standard form of y=(x-13)(x-12)?

Answer & Explanation

Madison Randolph

Madison Randolph

Expert

2022-02-04Added 20 answers

Explanation:
to put the equation into standard for we must multiply the terms on the right side of the equation. To multiply these two terms you multiply each individual term in the left parenthesis by each individual term in the right parenthesis.
y=(x-13)(x-12) becomes:
y=(x×x)(x×12)(13×x)+(13×12)
y=x212x13x+156
We can now combine like terms:
y=x2+(1213)x+156
y=x2+(25)x+156
y=x225x+156

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?